Environmental principles - Sadeleer, Nicolas de (Oxford University Press, 2002)
Environmental law has always responded to risks posed by industrial society but the new generation of risks have required a new set of environmental principles, emerging from a combination of public fears, science, ethics and established legal practice. This book shows how three of the most important principles of modern environmental law grew out of this new age of ecological risk: the polluter pays principle, the preventive principle and the precautionary principle. The author examines the legal force of these principles and in the process offers a novel theory of norm formation in environmental law by unearthing new grounds of legality